Magnetoresistance and structural characterization of electrospun La1−xSrxMnO3 nanowire network fabrics with x = 0.2. (March 2019) - Karwoth, Thomas; Zeng, Xian Lin; Koblischka, Michael R.; Hartmann, Uwe; Chang, Crosby; Hauet, Thomas; Li, Jian-Min
Abstract: Nonwoven nanowire network fabrics of the material class La1− x Sr x MnO3 (LSMO) with x  = 0.2 were fabricated employing a sol-gel-process via electrospinning and a subsequent thermal treatment process based on thermal gravity analysis results. Investigations by means of scanning electron microscopy revealed an average diameter of the resulting nanowires of around 230 nm and a length of more than 100 μm. The chemical phases of the samples have been confirmed via X-Ray diffraction. The nanowires are polycrystalline with an average grain size of about 25 nm obtained from transmission electron microscopy. Analyses of the electronic transportation properties and of the magnetoresistive (MR) effects of the nanowire samples were carried out by a four probe measurement inside a bath cryostat in fields up to 10 T. Measurements of magnetization in the temperature range 2 K <  T  < 350 K reveal the Curie temperature (325 K) and are compared to magnetic thermogravitmetric data. Magnetization loops M ( H ) at room temperature and 4.2 K were carried out revealing the soft magnetic character of the nanowires. Highlights: Polycrystalline nanowire networks of La1-x Srx MnO3 (x = 0.2) were prepared by electrospinning. Nanowire networks were characterized by X-ray, SEM and TEM. Magnetotransport properties have been measured between 2 K and 270 K. Magnetic properties were measured at 10 K and 300 K.